From awareness to action: ranking EU countries by consumer readiness to adopt sustainable products using a hybrid M–M methodology - Stojanović, Anđelka; Đorđević, Predrag; Shapkova Kocevska, Katerina; Tambovceva, Tatjana (Serbian Journal of Management, 2025)
In light of growing economic, environmental and sustainability challenges, increasingly more attention from policymakers, companies and researchers is being devoted to consumption patterns and understanding the factors that shape consumer behavior. The adoption of sustainable products within the European Union is actively promoted through a series of policies and initiatives aligned with the principles of the circular economy, to provide consumers with more transparent and accessible information, thereby empowering them to make eco-friendly choices. Nevertheless, consumer acceptance of sustainable products appears to vary considerably and is influenced by complex interactions among diverse factors. This study examines consumer readiness for sustainable products across twenty-seven EU countries using nine indicators across three dimensions: environmental awareness, financial readiness and trust in institutional sustainability mechanisms. A hybrid MEREC–MARCOS methodology was employed for ranking countries. This novel methodological approach allows for a detailed cross-country comparison and identification of areas for improving policies that incentivize sustainable consumption across the EU. Sweden emerges as the top-ranked country, followed by Cyprus and the Netherlands, while Latvia and Estonia rank lowest. The results suggest considerable divergence among EU Member States and potentially offer valuable insight into gaps in sustainable consumer behavior.
Keywords: consumer behavior; sustainable products; cross-country comparison; multi-criteria decision analysis (MCDA)